Examining the use of visualisation methods for the design of interactive systems - Li, Katie (Cranfield University, 2016)
Human-Computer Interaction (HCI) design has historically involved people from different fields. Designing HCI systems with people of varying background and expertise can bring different perspectives and ideas, but discipline-specific language and design methods can hinder such collaborations. The application of visualisation methods is a way to overcome these challenges, but to date selection tools tend to focus on a facet of HCI design methods and no research has been attempted to assemble a collection of HCI visualisation methods. To fill this gap, this research seeks to establish an inventory of HCI visualisation methods and identify ways of selecting amongst them. Creating the inventory of HCI methods would enable designers to discover and learn about methods that they may not have used before or be familiar with. Categorising the methods provides a structure for new and experienced designers to determine appropriate methods for their design project. The aim of this research is to support designers in the development of Human-Computer Interaction (HCI) systems through better selection and application of visualisation methods. This is achieved through four phases. In the first phase, three case studies are conducted to investigate the challenges and obstacles that influence the choice of a design approach in the development of HCI systems. The findings from the three case studies helped to form the design requirements for a visualisation methods selection and application guide. In the second phase, the Guide is developed. The third phase aims to evaluate the Guide. The Guide is employed in the development of a serious training game to demonstrate its applicability. In the fourth phase, a user study was designed to evaluate the serious training game. Through the evaluation of the serious training game, the Guide is validated. This research has contributed to the knowledge surrounding visualisation tools used in the design of interactive systems. The compilation of HCI visualisation methods establishes an inventory of methods for interaction design. The identification of Selection Approaches brings together the ways in which visualisation methods are organised and grouped. By mapping visualisation methods to Selection Approaches, this study has provided a way for practitioners to select a visualisation method to support their design practice. The development of the Selection Guide provided five filters, which helps designers to identify suitable visualisation methods based on the nature of the design challenge. The development of the Application Guide presented the methodology of each visualisation method in a consistent format. This enables the ease of method comparison and to ensure there is comprehensive information for each method. A user study showing the evaluation of a serious training game is presented. Two learning objectives were identified and mapped to Bloom’s Taxonomy to advocate an approach for like-to-like comparison with future studies.